Effects of sitagliptin therapy on markers of low-grade inflammation and cell adhesion molecules in patients with type 2 diabetes - Tremblay, André J.; Lamarche, Benoît; Deacon, Carolyn F.; Weisnagel, S. John; Couture, Patrick (Metabolism, clinical and experimental, 2014)
Inflammation and endothelial dysfunction are increasingly being recognized as key etiological factors in the development of atherosclerosis and subsequent cardiovascular disease. These pro-atherogenic factors are strongly correlated and are often found to co-segregate in patients with type 2 diabetes. The impact of sitagliptin, a selective inhibitor of dipeptidyl peptidase-4, on inflammation and markers of endothelial function remains to be fully characterized. The objective of the present study was to examine the effects of treatment with sitagliptin on the plasma levels of various markers of low-grade inflammation and cell adhesion molecules in patients with type 2 diabetes. Thirty-six subjects with type 2 diabetes (30 men/6 postmenopausal women with a mean age of 58.1±6.4years and a body mass index of 30.7±4.9kg/m2) were recruited into this double-blind, cross-over study using sitagliptin (100mg/d) or placebo, each for a 6-week period, including a 4-week washout period between the two phases. Blood samples were taken at the end of each phase of treatment. Compared with placebo, treatment with sitagliptin significantly reduced the plasma levels of C-reactive protein (CRP) (44.9%, P=0.006), interleukin (IL)-6 (24.7%, P=0.04), IL-18 (7.3%, P=0.004), secreted phospholipase-A2 (sPLA2) (12.9%, P=0.04), soluble intercellular adhesion molecule-1 (5.3%, P=0.002), and E-selectin (5.9%, P=0.005). A significant inverse correlation was found between changes in glucagon-like peptide-1 (GLP-1) and changes in CRP levels (r=0.41, P=0.01) following sitagliptin therapy. Sitagliptin therapy had more pronounced effects in subjects with higher levels of inflammatory markers and cell adhesion molecules compared with subjects with lower levels. Treatment with sitagliptin for 6weeks reduced plasma markers of low-grade inflammation and cell adhesion molecules, most likely by increasing plasma GLP-1 levels and improving glucose-insulin homeostasis. These beneficial effects of sitagliptin might represent a further advantage in the management of diabetes and its proatherogenic comorbidities.